'Are we becoming professionals?' Pre-service early childhood teachers' perceptions of the professionalism of early childhood teachers in Hong Kong. Issue 1 (1st January 2022) - Wong, Jessie Ming Sin
ABSTRACT: A long-neglected sector in education, early childhood education (ECE) in Hong Kong has generated much attention in recent years following the government's heavy promotion as laying the foundation for lifelong learning and all-round development. Enhancing 'teacher professionalism' by raising qualifications and remuneration is seen as a vehicle to achieve quality ECE. While the once lowly perceived occupation is now 'in fashion' among college applicants, little is known about how prospective teachers view ECE teachers' professionalism in Hong Kong. This study explored the views of 175 Hong Kong pre-service ECE teachers from 7 teacher education institutions using self-administered, open-ended survey questionnaires. The results showed that the pre-service ECE teachers generally described Hong Kong ECE teachers positively and viewed them as professionals. However, they also revealed a sharp dissonance between the participants' own perception and society's perception of the professionalism of ECE teachers due to the different emphases they used to define professionalism when shifting their perspectives. The results reflect a generally pessimistic view of the pre-service teachers on teaching in ECE as a career. Implications and suggestions for government policies, ECE teacher training, and research are discussed.